MOTIVATION OF THE ELDERLY TOWARDS MEDICAL TOURISM IN SUPHANBURI PROVINCE - Kotchasap, Pattida (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2022)
This research aimed to study the motivation of the elderly towards health tourism in Suporn Buri Province; to study the relationship between the factors of the service marketing mix affecting motivation. The sample consisted of 400elderly tourists who have experience with health activities for traveling in Suphanburi province. Most of them are male, age over 70 years old. They got bachelor's degree. Most of them are married. They have underlying diseases. However, they have good health habits and normally eat all 5 food groups. The researcher used questionnaires to collect the data and purposive sampling for data collection. The survey was conducted from October 1 and year 2020 to October 31 and year 2020 The statistics used for data analysis were frequency, percentage, mean, standard deviation, t-test, One-way ANOVA, and Multiple Comparisons: LSD Method and Pearson Product Moment Correlation Coefficient. The results of the research found are 1) the motivation of the elderly towards health tourism in Suphanburi Province was at the highest level in all aspects with the mean values in order of cultural, physical, interpersonal, and status and reputation. And service marketing mixed was at the highest level in all aspects with the mean values in order of process, price, physical evidence, product, people, promotion and place/distribution channel; 2) The motivation of the elderly towards health tourism in Suphanburi Province not different when difference group of gender, Education level and marital status, while, the motivation of the elderly towards health tourism in Suphanburi Province different when difference group of age and health behavior at significant of 0.05 level; 3) Elderly motivation towards health tourism in Suphanburi province has a high positive relationship with the overall service marketing mix factor at signification of 0.01 level. The motivation of the elderly towards health tourism in Suphanburi Province has a high positive relationship with personnel. The motivation of the elderly towards health tourism in Suphanburi Province has moderately positive relationship with place/ distribution channel. The motivation of the elderly towards health tourism in Suphanburi Province were lowest positive relationship with product, and the motivation of the elderly towards health tourism in Suphanburi Province were low positive relationship with price, promotion, process aspect and physical evidence at significant of 0.01 level.